Perbedaan Pemberian Rebusan Bayam Merah Dan Bayam Hijau Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Trimester II Dengan Anemia - Marina; Meita Ayu Damayanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
One thing to watch out for during pregnancy is anemia in pregnancy. One of the foods to increase hemoglobin levels in the blood is a decoction of red spinach and green spinach which can meet iron needs. The purpose of this study was to determine the relationship of giving red spinach and green spinach decoction to increase hemoglobin levels in second trimester pregnant women with anemia at TPMB Nuraeni, S.SiT. This study used PreExperimental research design with One Group Pretest-Postest design. The population in this study were second trimester pregnant women with anemia at TPMB Nuraeni, S.SiT with a sample size of 37 people. Data collection techniques were carried out with inclusion and exclusion criteria. After the data is obtained, data processing will be carried out through 4 stages, namely editing, coding, processing, and cleaning. After the data is processed, it will be analyzed using univariate analysis and bivariate analysis. From the results of data processing, it was found that there was an increase in average Hemoglobin to 12.40 gr/dL for the red spinach decoction intervention and 11.05 gr/dL for the green spinach decoction intervention. Based on these results, it can be concluded that red spinach is very important for increasing hemoglobin to maintain red blood cells for pregnant women which is beneficial for the fulfillment of fetal red blood cell mass, umbilical cord and placenta, and replacing blood lost during childbirth. So pregnant women are advised to consume red spinach stew and maintain food nutrition intake, it is highly recommended to eat foods that contain iron.